PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KUALITAS LABA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cut Hamdiah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2015)
The purpose of this study was to determine (1) the effect of both institutional ownership and earnings quality to the value of the transportation firm listed in Indonesia Stock Exchange (2) the effect of institutional ownership to the value o f the transportation firm listed in Indonesia Stock Exchange (3) the effect of earnings quality to the value of the transportation firm listed in Indonesia Stock Exchange.The population for this study is the Transportations firm listed in Indonesia Stock E xchange in 4 period of times (2009 2012), totaling 71 firm. All elements of the population are included and analysed. In other word, the study will be using census method. Due to differences in element of population in each year, data used are unbalanced p anel data. Analytical method used in this study is Multiple Linear Regression. The result is showed (1) institutional ownership and earnings quality have a significant effect to the value of the firm in simultaneous way (2) partially, institutional ownersh ip and earnings quality also have a significant effect to the value of the firm. In the future study researcher recommended to impose other variables from GCG mechanism such as; Independent Commissaries Board, Managerial Ownership, and Audit Quality.